Kajian Literatur Pengaruh Efiksasi Diri terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - Muhammad Awal Nur; Asmayani; R.N Alifiya (Universitas Adiwangsa Jambi, 2025)
This study aims to examine the role of student self-efficacy in improving mathematics learning outcomes. Efikasi diri is an seseorangal's belief in their ability to overcome challenges and achieve desired goals. This study uses a literature review method to gain a deeper understanding of the role of efikasi diri in mathematics learning. The results of the study show that student efikasi diri has a significant influence on motivation, perseverance, and effort in facing difficult academic tasks. Additionally, student efikasi diri also affects attitudes, mood, and efficiency in information processing. Therefore, it is important to create a supportive environment, provide constructive feedback, offer appropriate challenges, and develop student efikasi diri. By increasing student efikasi diri, it is expected that they will be more motivated, have confidence in their abilities, and be prepared to face challenges in learning mathematics.